A historical perspective on the OECD's 'humanitarian turn': PISA for Development and the Learning Framework 2030. Issue 4 (1st October 2020) - Xiaomin, Li; Auld, Euan
ABSTRACT: This paper identifies OECD's shifting agendas and approaches to education since inception and distinguishes three time periods. Each of these periods reflects shifting geopolitical and economic realities that shaped OECD's priorities and modes of operation. They also demonstrate the adaptive capacity and expansionist nature of OECD's education work as it successfully innovates, finds market niches and adds new dimensions to its datasets. These have culminated in its recent strategic initiatives, namely: PISA for Development and the Learning Framework 2030. The former aims to adapt PISA to fit into low- and middle-income countries and serve as the global learning metric; and the latter aims to incorporate non-cognitive competencies into its main tests. Together they are designed to expand and consolidate the Organisation's influence in the context of the SDGs. By adopting a historical perspective, we provide a critical understanding of OECD's shifting role in global education governance and its 'humanitarian turn.